Effective leadership theory and practice - Franko, Joshia (Willford Press, 2019)
Leadership is the practice of leading or guiding individuals, teams or organizations. Research and studies in this field have led to the formulation of theories that seek to comprehend the dynamics of power, vision, behavior, charisma, intelligence, situational interaction, etc. The emergence of a leader can happen in a variety of different situations and tasks. Intelligence, conscientiousness, adjusment, self-efficacy, extraversion and openness to experience are some of the qualities that play a positive role in the emergence of a leader. Some of the other factors that affect the emergence of leadership are gender identity, dominance, emotional intelligence, assertiveness, self-monitoring, character strength, etc. Different leadership styles suit different situations. These can be classified as authoritarian, Laissez-faire, participative, task-oriented and relationship-oriented. This book presents researches and studies performed by experts across the globe on the varied aspects of effective leadership. It is compiled in such a manner, that it will provide in-depth knowledge about the theory and practice of leadership. The book is appropriate for students seeking detailed information in this area as well as for experts.